R.M. Steamer in Carenage, Grenada - (:unkn) unknown (My University, 2009)
R.M. Steamer anchored in The Carenage, Grenada's picturesque "U-shaped" harbour, with buildings surrounding the waterfront and mountain range in the background. Affixed to the postcard is a 2 cents US stamp, postmarked February 18th, 1907.
Colour: Re-coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Postcards; Grenada; Harbors--Grenada; Ships--Grenada; 1907; Steamboats--Grenada; Buildings--Grenada; Mountains--Grenada; Cities and towns--Grenada--St. Georges; Commercial buildings--Grenada; Carenage, The (Grenada)